2022
DOI: 10.1186/s12544-022-00534-5
|View full text |Cite
|
Sign up to set email alerts
|

Configuring user information by considering trust threatening factors associated with automated vehicles

Abstract: Background The accelerated development of automated driving technology has raised the expectation that commercially available automated vehicles will be increasingly become ubiquitous. It has been claimed that automated vehicles are safer than conventional manual vehicles, leading to the expectation of fewer accidents. However, people expect not only better but also near-perfect machines. Given that accidents involving automated vehicle do occur and are highlighted by the media, negative reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous research has examined various aspects and underlying determinants of passenger trust in automated vehicles, including the requirements and effects of feedback from the automated driving system via in-vehicle human-machine interfaces (HMIs; e.g., Colley et al, 2020;Feierle et al, 2020;Hartwich et al, 2021;Wintersberger et al, 2021;Yun & Yang, 2022;see Ekman et al, 2017 for a trust-based framework for HMI design), uncertainty displays (e.g., Beller et al, 2013;Helldin et al, 2013), automation malfunctions (e.g., Feierle et al, 2021), overtrust (e.g., Victor et al, 2018), driving behavior and style (e.g., Ekman et al, 2019;Mühl et al, 2020), and initial or introductory information (e.g., Forster et al, 2018;Körber et al, 2018) on self-reported passenger trust.…”
Section: Previous Research On Risk Perception and Trust Of Passengers...mentioning
confidence: 99%
“…Previous research has examined various aspects and underlying determinants of passenger trust in automated vehicles, including the requirements and effects of feedback from the automated driving system via in-vehicle human-machine interfaces (HMIs; e.g., Colley et al, 2020;Feierle et al, 2020;Hartwich et al, 2021;Wintersberger et al, 2021;Yun & Yang, 2022;see Ekman et al, 2017 for a trust-based framework for HMI design), uncertainty displays (e.g., Beller et al, 2013;Helldin et al, 2013), automation malfunctions (e.g., Feierle et al, 2021), overtrust (e.g., Victor et al, 2018), driving behavior and style (e.g., Ekman et al, 2019;Mühl et al, 2020), and initial or introductory information (e.g., Forster et al, 2018;Körber et al, 2018) on self-reported passenger trust.…”
Section: Previous Research On Risk Perception and Trust Of Passengers...mentioning
confidence: 99%